ESTIMASI SUMBER DAYA ANDESIT MENGGUNAKAN METODE CROSS SECTION PT. AKAM DI KABUPATEN SORONG PROVINSI PAPUA BARAT - Aldi F. Valderama; Ricardo O.M. Hutapea (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2018)
One of technical requirements in renewing mining operation permits, according to ‘Peraturan Menteri Energi dan Sumber Daya Mineral Nomor 34 Tahun 2017’, is the balance sheet of resources and reserves. Before the expiration of the production permit of PT. AKAM, it was then needed to calculate the andesite resource in the operation area of PT. AKAM in Sorong, Papua Barat. The Cross Section method is considered to be the best way to estimate the andesite resource because this method can be utilised to find out the layout of the overburden and mineral. The results highlighted that andesite resource in the operation area of PT. AKAM was approximately 405.780.313 m³, with a cover layer of 498,937 m³. The productivity age of PT. AKAM is predicted to be 49,64 years, with the annual production of 8.112 m³